SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA DOSEN DENGAN METODE AHP DAN SAW - Al Fath Riza Kholdani; Muflih; Nur Arminarahmah (Fakultas Teknik Universitas Lambung Mangkurat, 2017)
Assessment of lecturer's performance so far is done by excel calculation and still very subjektif. This study discusses and makes an Application Decision Support System Assessment Performance Lecturer Islamic University of Kalimantan MAB Faculty of Information Technology Using AHP and SAW Method to obtain results that accuracy and validity high computerized. The calculation of student quesioner, peer, leader and self using SAW method, then its value becomes new criteria combined with internal academic calculation that is learning, research, dedication and guidance using AHP method result is final decision 8.